Therapeutic potential of extracellular vesicles derived from cardiac progenitor cells in rodent models of chemotherapy-induced cardiomyopathy - Desgres, Manon; Lima Correa, Bruna; Petrusca, Lorena; Autret, Gwennhael; Pezzana, Chloé; Marigny, Céline; Guillas, Chloé; Bellamy, Valérie; Vilar, José; Perier, Marie-Cécile; Dingli, Florent; Loew, Damarys; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: Current treatments of chemotherapy-induced cardiomyopathy (CCM) are of limited efficacy. We assessed whether repeated intravenous injections of human extracellular vesicles from cardiac progenitor cells (EV-CPC) could represent a new therapeutic option and whether EV manufacturing according to a Good Manufacturing Practices (GMP)-compatible process did not impair their bioactivity. Methods: Immuno-competent mice received intra-peritoneal injections (IP) of doxorubicin (DOX) (4 mg/kg each; cumulative dose: 12 mg/kg) and were then intravenously (IV) injected three times with EV-CPC (total dose: 30 billion). Cardiac function was assessed 9-11 weeks later by cardiac magnetic resonance imaging (CMR) using strain as the primary end point. Then, immuno-competent rats received 5 IP injections of DOX (3 mg/kg each; cumulative dose 15mg/kg) followed by 3 equal IV injections of GMP-EV (total dose: 100 billion). Cardiac function was assessed by two dimensional-echocardiography. Results: In the chronic mouse model of CCM, DOX+placebo-injected hearts incurred a significant decline in basal (global, epi- and endocardial) circumferential strain compared with sham DOX-untreated mice (p=0.043, p=0.042, p=0.048 respectively) while EV-CPC preserved these indices. Global longitudinal strain followed a similar pattern. In the rat model, IV injections of GMP-EV also preserved left ventricular end-systolic and end-diastolic volumes compared with untreated controls. Conclusions: Intravenously-injected extracellular vesicles derived from CPC have cardio-protective effects which may make them an attractive user-friendly option for the treatment of CCM.